Brazilian fruit pulps as functional foods and additives: Evaluation of bioactive compounds. (1st April 2015) - Paz, Mário; Gúllon, Patricia; Barroso, M. Fátima; Carvalho, Ana P.; Domingues, Valentina F.; Gomes, Ana M.; Becker, Helena; Longhinotti, Elisane; Delerue-Matos, Cristina
Highlights: Antibacterial and antioxidant capacities of eight tropical fruits were evaluated. Tamarind extracts have activity against Gram positive and Gram negative bacteria. Acerola and açaí presented the highest antioxidant capacities. There is a reverse relationship between these two activities. Abstract: Eight tropical fruit pulps from Brazil were simultaneously characterised in terms of their antioxidant and antimicrobial properties. Antioxidant activity was screened by DPPH radical scavenging activity (126–3987 mg TE/100 g DW) and ferric reduction activity power (368–20819 mg AAE/100 g DW), and complemented with total phenolic content (329–12466 mg GAE/100 g DW) and total flavonoid content measurements (46–672 mg EE /100 g DW), whereas antimicrobial activity was tested against the most frequently found food pathogens. Acerola and açaí presented the highest values for the antioxidant-related measurements. Direct correlations between these measurements could be observed for some of the fruits. Tamarind exhibited the broadest antimicrobial potential, having revealed growth inhibition of Pseudomonas aeruginosa . Escherichia coli, Listeria monocytogenes, Salmonella sp. and Staphylococcus aureus . Açaí and tamarind extracts presented an inverse relationship between antibacterial and antioxidant activities, and therefore, the antibacterial activity cannot be attributed (only) to phenolic compounds.